Spicework Implementation On Linux Operating System Ubuntu Server For Network Monitoring At Smk n 1 Kota Bengkulu - Ahmad Rivaldo; Reno Supardi; Abdussalam Al Akbar (Jurnal Komputer, Informasi dan Teknologi, 2023)
One system that can monitor computer networks is using spicework. Spiceworks monitors based on the ip address of the computer connected to the network, spicework in monitoring the network requires high hardware specifications of at least 4GB memory. A system that can monitor the network does not yet exist on the SMK N 1 Bengkulu City network, the computer network at SMK N 1 Bengkulu City is used by students, teachers and TU, libraries and for other purposes, in addition to knowing whether or not the computer is connected to the SMK N 1 Bengkulu City computer network, it can also be used to monitor the resources (hard disk and memory) of the device. In doing so.